Univerbizované výrazy odvozené sufixy od slov s časovým významem - Kolářová , Ivana (Stylistyka, 2021)
We are going to deal with the simple expressions with components -minutovka, -hodi- novka, -letka (dvouletka, pet Hetka..and with other simple expressions (trvalka, ćasov- ka...) that have been derived from phrases and compound expressions with the adjectives with components -minutovy, -hodinovy, ćasovy (ćasovka), -lety (dvoulety, petilety, from verbal adjective trvaly (Jrvalka). We are gong to research the frequence of the simple expressions dvacetiminutovka, desetiminutovka, dvouhodinovka, ćasovka, trvalka, dvouletka, petiletka... into the texts of Czech national corpus SYN2000 and to compare the freąuence of them with the frequence of phrases and compound expressions desetiminutova hra, petiminutove preruśeni hry, hodinoyy zavod, ćtyriadvacetihodinovy maraton, vytrvala rostlina, ćasovyzavod,jlzda na ćas and all that and appearance of them in various types of texts.